Quantitative sensory testing in children with sickle cell disease: additional insights and future possibilities. (28th March 2019) - Miller, Robin E.; Brown, Dawn S.; Keith, Scott W.; Hegarty, Sarah E.; Setty, Yamaja; Campbell, Claudia M.; McCahan, Suzanne M.; Gayen‐Betal, Suhita; Byck, Hal; Stuart, Marie
Summary: Quantitative sensory testing (QST) is used in a variety of pain disorders to characterize pain and predict prognosis and response to specific therapies. In this study, we aimed to confirm results in the literature documenting altered QST thresholds in sickle cell disease (SCD) and assess the test–retest reliability of results over time. Fifty‐seven SCD and 60 control subjects aged 8–20 years underwent heat and cold detection and pain threshold testing using a Medoc TSAII. Participants were tested at baseline and 3 months; SCD subjects were additionally tested at 6 months. An important facet of our study was the development and use of a novel QST modelling approach, allowing us to model all data together across modalities. We have not demonstrated significant differences in thermal thresholds between subjects with SCD and controls. Thermal thresholds were consistent over a 3‐ to 6‐month period. Subjects on whom hydroxycarbamide (HC) was initiated shortly before or after baseline testing (new HC users) exhibited progressive decreases in thermal sensitivity from baseline to 6 months, suggesting that thermal testing may be sensitive to effective therapy to prevent vasoocclusive pain. These findings inform the use of QST as an endpoint in the evaluation of preventative pain therapies.